Identifying Predictors of Acquired Velopharyngeal Insufficiency in Cleft Lip and Palate Following Maxillary Osteotomy Using Multiple Regression Analyses. Issue 8 (November 2020) - Pereira, Valerie J.; Tuomainen, Jyrki; Hay, Norman; Mars, Michael; Suchak, Archna; Sell, Debbie A.
Abstract : Background: Maxillary osteotomy is typically undertaken to correct abnormal facial growth in cleft lip and palate. The surgery can cause velopharyngeal insufficiency resulting in hypernasality. This study aims to identify valid predictors of acquired velopharyngeal insufficiency following maxillary osteotomy by using a range of perceptual and instrumental speech investigations and multiple regression. Methods: A prospective study was undertaken consisting of a consecutive series of patients with cleft lip and palate (N = 20) undergoing maxillary osteotomy by a single surgeon. Participants were seen at: 0 to 3 months pre-surgery (T1), 3-months (T2), and 12-months (T3) post-surgery. Hypernasality was rated using the cleft audit protocol for speech-augmented (CAPS-A) and visual analog scales, and nasalance was measured on the Nasometer II 6400. For lateral videofluorosopic and nasendoscopic images, visual perceptual ratings and quantitative ratiometric measurements were undertaken. Multiple regression analyses were undertaken to identify predictors. Results: T3 models with hypernasality as the dependent variable were found to be a good fit and significant (eg, CAPS-A: R 2 = 0.920, F (11, 7) = 7.303, P  = 0.007). Closure ratio (a quantitative ratiometric measurement) and proportion of palate contacting the posterior pharyngeal wall (a visual perceptual rating) were identified as significant predictors for the CAPS-A model ( P  = 0.030, P  = 0.002). Abstract : Supplemental Digital Content is available in the text